Mitochondrial Diabetes A Rare Case - Singh, Arun Kumar; Msasko, Aoki; Miyata, Midori; Mine, Yasuke; Suzuki, Junichi; Urakami, Tatsuhiko (Journal of Nepal Paediatric Society, 2018)
A 25 years female diagnosed and confirmed mitochondrial by gene analysis mutation DNA 3243(A-G). CQ10 was useful for the resolution of clinical symptoms, and metformin should be avoided in mito-chondrial diabetes.